The Role of Familial Mediterranean Fever Gene Mutation in Treatment of Infantile Colitis With Resistant Perianal Fistula - Maşallah BARAN; Yeliz ÇAĞAN APPAK; Pınar GARİPCİN and Yavuz DEMİRÇELİK and; Ebru PALA and; ÖZYILMAZ and; y KARAKOYUN and; n ERGÜN (Archives of Rheumatology, 2018)
Symptoms of infantile inflammatory bowel disease (I-IBD) can be life-threatening and associated with poor prognosis. The presence of Mediterranean fever (MEFV) gene mutations play an important role in treatment of I-IBD. In this article, we describe a case of I-IBD with a resistant fistula, in which remission occurred following colchicine therapy. The patient was a six-month-girl with complaints of bloody diarrhea and a perianal abscess of three months duration. Laboratory tests revealed elevated inflammatory parameters, hypoalbuminemia, and anemia. Results of repeated viral, bacterial and parasitic analyses were negative. Endoscopic and histopathological examinations confirmed a diagnosis of I-IBD. Although diarrhea episodes decreased following intensive conventional treatment with immunosuppressive therapy and anti-tumor necrosis factor, the perianal abscess and fistula did not resolve. Molecular genetic analysis to identify causes of infantile disease revealed the MEFV gene mutation. Thus, colchicine was added to the treatment regimen. Following treatment with colchicine, defecation returned to normal, and the fistula resolved. The MEFV gene mutation should be investigated in children with infantile colitis and resistant fistulas, particularly in Mediterranean countries. In patients with infantile colitis who have the MEFV gene mutation, colchicine treatment may be an alternative to intensive immunosuppressive therapy.